Worldview foundations of studying secularity - (:unkn) unknown (Serials Publications, 2017)
In the modern world, the tendencies of secularization are in a complex interaction with the traditional and new forms of influence of religion on the social and individual consciousness, on the socio-political processes and institutions. In the society, intense public and academic discussions take place on the question of what a secular state should be or should not be. However, the social and humanitarian sciences have not yet developed a generally accepted conceptual and methodological approach to resolving the issues of the relation between the secular and the religious, between faith and knowledge. The decline of religious faith as a worldview and a mental structure, as a disciplinary-upbringing institution of socialization, as a spiritual and moral core of the life of the individual is indubitable. Religiosity is shifting more and more towards an external, largely ostentatious, image-related style of behavior, whereas secularism is becoming the worldview basis of modernity. The article substantiates the idea that freethinking is the basis for developing a categorical apparatus and an authentic methodology for investigating the problems of secularity. © Serials Publications.
Keywords: (Post) secularism; Politics; Religion; Secularity; Society; Worldview.